The fate of financial secrecy under the new global tax system - Batache, Leila (Journal of Human Sciences, 2023)
This study seeks to ascertain the impact of bank secrecy on the tax evasion, and the role of new standards and international cooperation mechanisms in setting limits on bank secrecy and preventing it from being an obstacle to transparency of information. In the face of this confrontation between the rules governing confidentiality and the new international trend, the question arises as to the impact of this regime on the right to financial secrecy? We have decided to examine the frameworks of the new tax system in view of the conflict between the customer’s right to financial privacy and the duty to address tax evasion. The results of the study showed that international efforts to combat tax evasion, have largely managed to establish limits on secrecy, especially with regard to tax matters through the imposition of automatic disclosure of information.